Pseudomonas aeruginosa: A Bacterial Platform for Biopharmaceutical Production - Doumit Camilios-Neto; Rodolfo Ricken do Nascimento; Jonathan Ratko; Nicole Caldas Pan; Rubia Casagrande; Waldiceu A. Verri; Josiane A. Vignoli (Future Pharmacology)
Pseudomonas aeruginosa is a metabolically versatile opportunistic pathogen capable of surviving in a range of environments. The major contribution to these abilities relies on virulence factor production, e.g., exotoxins, phenazines, and rhamnolipids, regulated through a hierarchical system of communication, named quorum sensing (QS). QS involves the production, release, and recognition of two classes of diffusible signal molecules: N-acyl-homoserine lactones and alkyl-quinolones. These present a central role during P. aeruginosa infection, regulating bacterial virulence and the modulation of the host immune system. The influence of this arsenal of virulence factors on bacterial–host interaction makes P. aeruginosa a highly potential platform for the development of biopharmaceuticals. Here, we comprehensively reviewed the therapeutical applications of P. aeruginosa virulence factors and quorum sensing signaling molecules on pathological conditions, ranging from infections and inflammation to cancer disease.